Rapid Resolution of Life-Threatening Hypertriglyceridemia after Evinacumab Administration in a Pediatric HSCT Recipient: A Case Report - Alice Fachin; Chiara De Carlo; Alessandra Maestro; Davide Zanon; Egidio Barbi; Natalia Maximova (MDPI AG, 2023)
Evinacumab, a human monoclonal antibody against angiopoietin-like protein 3 (ANGPTL3), has recently been approved by the U.S. Food and Drug Administration as an add-on therapy for homozygous familial hypercholesterolemia (HoFH) in patients of 12 years and older. Its role as a triglyceride-lowering drug is also emerging in the literature. However, it has not been approved for this indication yet, neither in the adult nor in the pediatric population. We describe the case of a 10-year-old boy who underwent an allogeneic hematopoietic stem cell transplant for acute lymphoblastic leukemia complicated by chronic graft-versus-host disease (GVHD) and presented life-threatening refractory hypertriglyceridemia due to the concomitant use of ruxolitinib and sirolimus. After the failure of the insulin treatment and due to the technical impossibility of performing lipid apheresis, the child underwent evinacumab treatment, obtaining a dramatic rapid reduction in triglyceride and cholesterol levels. This is the first report of a pediatric patient younger than 12 years in Europe receiving evinacumab to treat severe hypertriglyceridemia. The therapy with angiopoietin-like proteins inhibitors has been effective, safe, and well-tolerated in our patient, suggesting that evinacumab may be used in the pediatric population when other therapeutic strategies are ineffective or contraindicated.